Relation between Gender and Sexual Orientation from the Evolutionary Approach - Beckmann Menezes, Aline (2010)
This study addresses the relationship between gender and sexual orientation from the interacionist perspective of Evolutionary Psychology and the analysis of various aspects of human sexuality. This article aimed to discuss existing literature about gender and sexual orientation, based on four questions of Ethology. It’s proposed that sexual orientation has multiple origins, and that one of those is related to typical patterns of gender and gender identity. This would lead to identification with same-sex or opposite-sex individuals, and hence, to the attraction for the group different from the one to which identification was established. This approach integrates biological pre-dispositions to the analysis of cultural influences, understanding, as complementary, theoretical views that are usually stated as contradictory.